Exploring the Efficacy of Kitab Al-Af'al Al-Yawmiyyah in Arabic Language Acquisition among Malaysian Female Students - Baharun, Segaf; Arisandi, Yusuf; Husein, Achmad Fairuz; Salsabil, Aufa Hanin (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study investigates the efficacy of Kitab al-Afʿāl al-Yawmiyyah in enhancing Arabic language acquisition among Malaysian female students. Using a quasi-experimental mixed-methods design, the study involved 30 intermediate-level students in a Kedah Islamic boarding school participated in a six-week program centered on daily verb use with a focus on feminine forms. Data were collected through pre- and post-tests, classroom observations, and semi-structured interviews. Quantitative analysis showed a significant increase in vocabulary mastery, with post-test scores yielding a large effect size (Cohen’s d = 1.78). Qualitative findings revealed that the kitab strengthened students’ confidence, raised awareness of gender-appropriate verb forms, and encouraged consistent use of the feminine plural suffix -na in oral communication. The study concludes that Kitab al-Afʿāl al-Yawmiyyah is an effective and identity-affirming resource for promoting inclusive and accurate Arabic pedagogy for female learners in Malaysia.